Characterization and compaction of thermal Power Plant ashes used in road embankments - Calzada Pérez, Miguel Ángel (2025)
The shortage of energy resources and raw materials advises to use industrial wastes and subproducts. One area where they can be used is in road construction, getting valid and economical structural solutions, capable of improving the land and the environment.  In this paper, the results and conclusions or a study of ashes characterization from two thermal power plants in Spain, located in the towns of Soto de Ribera and Aboño (Asturias, Spain) are described, for its possible application in the construction of road embankments and fillings.